2005
DOI: 10.1055/s-2005-837736
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcome Following Exposure to Permethrin and Use of Teratogen Information

Abstract: NIX is a 1% permethrin creme rinse used for the treatment of head lice. There are no studies regarding human exposure during pregnancy. The primary objective of this study was to examine the safety of permethrin exposure during pregnancy. The secondary objective was to examine how teratogen information is perceived and used by women who requested information regarding this product. Women who had called the Motherisk and MotherSafe Programs to inquire about exposure to permethrin during pregnancy were followed-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 7 publications
1
21
1
1
Order By: Relevance
“…Many studies have reported no increased risk of CAs in offspring residing in areas with pesticide use (de Siqueira et al, 2010; Marshall et al, 1997). Potential association between permethrin/benzyl benzoate lotion during pregnancy for therapeutic reasons (headlice and/or scabies treatment) and CAs was investigated in one study (Kennedy et al, 2005) concluding that no association exists and thus these pesticides are safe. However, the main limitation of this study was the small number of exposed women during the first trimester of pregnancy, when the child is more susceptible to developmental CAs (Kennedy et al, 2005).…”
Section: Pesticides and Development Of Congenital Abnormalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported no increased risk of CAs in offspring residing in areas with pesticide use (de Siqueira et al, 2010; Marshall et al, 1997). Potential association between permethrin/benzyl benzoate lotion during pregnancy for therapeutic reasons (headlice and/or scabies treatment) and CAs was investigated in one study (Kennedy et al, 2005) concluding that no association exists and thus these pesticides are safe. However, the main limitation of this study was the small number of exposed women during the first trimester of pregnancy, when the child is more susceptible to developmental CAs (Kennedy et al, 2005).…”
Section: Pesticides and Development Of Congenital Abnormalitiesmentioning
confidence: 99%
“…Potential association between permethrin/benzyl benzoate lotion during pregnancy for therapeutic reasons (headlice and/or scabies treatment) and CAs was investigated in one study (Kennedy et al, 2005) concluding that no association exists and thus these pesticides are safe. However, the main limitation of this study was the small number of exposed women during the first trimester of pregnancy, when the child is more susceptible to developmental CAs (Kennedy et al, 2005). An exposure-dependent positive link between maternal residence in near toxic waste sites in New York state and CAs and an increased risk for MSAs (OR = 1.2, 95%C = 1.05–1.38) and pesticide exposure was reported (Geschwind et al, 1992) but these results could not be replicated in a following study done in California (Croen et al, 1997).…”
Section: Pesticides and Development Of Congenital Abnormalitiesmentioning
confidence: 99%
“…In a prospective study of 113 pregnant women, who were A C C E P T E D M A N U S C R I P T exposed to permethrin (31 during the 1 st trimester), no differences in live births, spontaneous abortions, major malformations, birth weight, and gestational age at delivery were observed when compared to matched controls. 77 This was supported in a study of 196 pregnant women exposed to permethrin. 78 Precipitated sulfur and benzyl benzoate 25% lotion are second-line treatments; however, they are less effective than permethrin.…”
Section: Scabiesmentioning
confidence: 85%
“…Due to its long-term effect, it is considered more effective than pyrethrum for lice infestation, although there are no comparative studies available on the two substances. The prospective study of 113 pregnant women who used permethrin shampoo (31 in the first trimester) gave no indication of an embryotoxic risk (Kennedy 2005). Mytton (2007) also found nothing remarkable among 196 pregnant women treated with permethrin.…”
Section: Lice Medicationsmentioning
confidence: 97%